ANALYSIS OF SUNFLOWER AREAS’ PHYTO-PATHOGENIC CONDITION DURING VEGETATION PERIOD UNDER DIFFERENT AGRO-CLIMATIC CONDITIONS - Pospelov, S. V.; Pospielova, G. D.; Nechiporenko, N. I.; Mishchenko, O. V.; Cherniak О. О.; Skliar, S. S.; Ivanichko, O. V. (Scientific Progress & Innovations, 2021)
Under modern farming conditions in Ukraine, considerable crop rotation upsetting is taking place, which at the background of climate change has led to considerable deterioration of phyto-sanitary situation and massive development of destructive processes in sunflower agro-ecosystem. The purpose of the research was to study the level of development and spreading of sunflower diseases during vegetation period and their dependence on agro-climatic indicators. During 2020–2021, the phyto-pathological condition of two sunflower hybrids – NK Alegro (mid-early) and Opera PR (mid-ripening), cultivated in Myrhorod district, Poltava region, was studied. The investigation of the sown areas was conducted at definite periods of the plant vegetation to detect several diseases. It was determined that the signs of white and grey rots were observed on Opera PR and NK Alegro sunflower hybrids beginning from the phase of 3–4 pairs of true leaves till head formation. The disease spreading in 2020 did not exceed 2.0–2.5 % at 0.8 maximum development. In 2021, the phyto-sanitary condition deteriorated and rot spreading in the phase of head formation made 2.9 % at 1.5 % development. The investigation of sunflower fields in 2020 enabled to detect insignificant development of false mildew with the maximum spreading at the phase of 4–6 pairs of leaves – 0.8–1.3 %, while in 2021, the disease reached its maximum level in the phase of head formation – 3.0–3.5 %, which was connected with agro-climatic conditions of the vegetation period. Black spots (phomosis) were observed during the years of study, their spreading did not exceed 7.6 % in 2020, and increased by almost 5 times (32.5–34.0 %) in 2021. Dry rot of heads was also detected at the level of 6.5–9.5 % in 2020, and it increased to 8.5–11.0 % in 2021. The conducted studies enabled to reveal sunflower suckers, the degree of their populating plants made 1.8–2.4 % (in 2020) and 3.2–4.5 % (in 2021), and the degree of affection – 1 point, which corresponded to the low level.